Optimizing Students' Qur'an Memorization Through the Tikrar Method at SDN 41 Padang - Ikhlas, Zaitul; Batubara, Juliana; Sabri, Ahmad (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
Qur’anic literacy from an early age holds a crucial role in shaping the Islamic character of students, particularly at the elementary education level. However, the memorization achievements of Qur’an among students in public elementary schools remain varied and suboptimal. This study aims to analyze the effectiveness of the Tikrar method in improving Qur’an memorization skills among students at SDN 41 Padang. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. A total of 32 students were selected through purposive sampling. Data were collected through pretest and posttest memorization assessments and analyzed using the paired sample t-test with SPSS. The results showed a significant improvement in the experimental group compared to the control group (p-value = 0.000), indicating that the Tikrar method is effective in enhancing Qur’an memorization among public elementary school students. This study contributes to the reinforcement of Qur’anic literacy in schools and offers practical guidance in implementing a structured memorization method. It concludes that the Tikrar method can serve as an effective learning strategy to support the development of Islamic character education. Further research is recommended to be conducted over a longer period and to incorporate digital media to optimize students' memorization retention.